Fiscal Tax Law Perspective in Realizing Justice and Efficiency: Critical Analysis of Applicable Tax Regulations - Wahyuni, Fitri (International Journal of Science and Society, 2024)
This research aims to explore the role of the fiscal tax law perspective in realising justice and efficiency in the tax system by applying critical analysis of applicable tax regulations. The research method involves an in-depth review of applicable tax regulations and data collection through related literature. This research methodology consists of three main approaches: normative juridical, literature studies as a data collection method and case studies on implementing tax regulations. The research results show an imbalance in the implementation of current tax regulations, which can affect the achievement of justice and efficiency goals. This research also identifies several aspects that require deeper attention to improve tax effectiveness and fairness. Reforms in terms of transparency, accuracy of tax rates, and simplification of tax regulations are important steps to achieve these goals through critical analysis of applicable tax regulations.